The Efficacy of Inside-Out Transversus Abdominis Plane Block vs Local Infiltration before Wound Closure in Pain Management after Kidney Transplantation: A Double-blind, Randomized Trial - Chatporn Boonyapalanant (2022)
Objective: Transversus abdominis plane (TAP) block is a form of multimodal pain management in open abdominal surgery. Among patients who undergo kidney transplantation, their choice of painkillers is limited. This study aims to determine the efficacy of TAP block vs local infiltration in pain management after kidney transplantation. Materials and Methods: In this prospective, randomized, double-blinded clinical trial, 46 patients with end-stage kidney disease who had undergone kidney transplantation were randomly divided into two groups: a local anesthetic infiltration (LA) group receiving 0.25% Bupivacaine 20 ml around the surgical wound before wound closure and a TAP block group receiving 0.25% Bupivacaine 20 ml by the inside-out technique. Their postoperative pain scores and morphine consumption were recorded at 2, 6, 12, 18, 24, and 48 hours. Results: There was no statistically significant difference in the baseline characteristics between the groups. The postoperative pain score at two hours in the TAP block group was significantly lower than in the LA group (P value = 0.037), but without other differences in their pain scores after two hours. There was no statistical difference in the morphine consumption between the two groups. The total morphine consumption in the TAP block group was less than in the LA group, but this was not statistically significant. No patients suffered from complications of the TAP block. Conclusion: Transversus abdominis plane block can reduce postoperative pain at two hours after kidney transplantation, without significant complications.